KEPATUHAN TENAGA MEDIS DALAM MENGGUNAKAN APD DI BANGSAL COVID : STUDI KASUS DI RS X SEMARANG - Ryna Mahdalena Ambarita; Antono Suryoputro; Yuliani Setyaningsih (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Covid-19 spreads massively and very fast in transmission. Health workers who work in hospitals were very vulnerable to being exposed to the Covid-19 virus. The used of personal protective equipment was very important for medical personnel serving patients in the Covid Ward to minimize the risk of transmission. The purpose of this study was to determine the factors associated with compliance with the use of personal protective equipment for health workers in the Covid Ward. This study was a quantitative study with the number of samples being the total population of Health workers on duty in the Covid Ward as many as 61 respondents. Statistical analysis was carried out using the Spearman Rho test. The results showed that there was no relationship between age (p = 0.406), education (p = 0.351), years of service (p = 0.216), knowledge (p = 0.344), attitudes (p = 0.434), availability (p = 0.328), and supervision (p=0.534) with the compliance of medical personnel in using personal protective equipment in the Covid Ward of RS X Semarang City. It was necessary to carry out sudden periodic inspections by the PPI team and the OHS team of RS X. And awards are given to health workers who comply with using personal protective equipment in addition to having imposed strict sanctions if health workers do not use personal protective equipment.